'Each flight is different': Carbon emissions of selected flights in three geographical markets. (December 2017) - Baumeister, Stefan
Highlights: Carbon emissions of flights in three geographical markets have been compared. It was found that carbon emissions of individual flights differ tremendously. Flying on the most modern aircraft is not always the least polluting option. A flight with two stopovers can be less polluting than a non-stop flight. Abstract: Air travel is considered the biggest individual climate sin. Avoiding flying, however, seems impossible. In this paper we argue that the flight a passenger chooses can be significant. For this purpose we compared the carbon emissions of selected flights in three geographical markets. We found tremendous differences in the environmental performance of individual flights. Furthermore, we also found that flying with the most modern aircraft or flying non-stop represents, in many cases, the least polluting option. Nevertheless, we were able to show that there are exceptions to this rule. Based on our results, we provide recommendations to the industry and for further research.